Plan estratégico para la mecánica automotriz Palda de la ciudad de Loja, provincia de Loja - Palacios Jaramillo, Andrehina Kymberlith (2015)
This thesis has as main objective to design a strategic plan for Palda AUTOMOTIVE MECHANIC considering it as a tool to efficiently organize the same activities and decision-making for better performance. In developing the use of methods such as historical, deductive, inductive and descriptive method was necessary techniques were applied as direct observation, one interview the manager owner of mechanics and two surveys, one to 10 employees was applied mechanics and over 296 regular customers; Specific objectives were focused on developing a current diagnosis of mechanics, also an external analysis was performed considering the economic-financial, political, legal and environmental, social, cultural and technological factors, where opportunities and threats detected mechanics, the same that were evaluated through the matrix efe, obtaining a total of 2.86 points, which means that the mechanical has more opportunities than threats; after this internal analysis which identified the strengths and weaknesses of mechanics through the efi matrix, with a total of 2.78 points was performed; which helped build the SWOT matrix and the matrix of High Impact determining the strategies of the objectives of the strategic plan were obtained with a total cost of $ 21,180.92, then the objectives that served to raise the proposal are described below: 1. Implement a management software garages, it will serve for management of engineering to better develop its administrative activities, this lens has a costof$1,070.00. 2. Implement a manual functions, through this lens mechanics will have a tool that allows employees to clearly understand their duties and responsibilities prevent leakage of this objective no cost to the mechanics. 3. Implement a regulation Admission and Employment, this regulation will allow the manager of mechanics have a guiding tool for recruitment and selection of appropriate staff, this goal does not require funding. 4. Implement an advertising plan, this objective is to achieve positioning in the minds of current and future customers, it requires a value of $ 1,413.00, for implementation. 5. Implement the moving mechanical express service, the implementation of this objective will support the increased customer base, it requires a value of $ 16,962.42 for execution. In the conclusions it was determined that the silver targets were met in full, ie the development of a strategic plan to the company to take advantage of a better way resources are there. So it is recommended to implement this strategic plan considering the situation assessment and internal, external and strategic objectives identified in the research factors